2015
DOI: 10.1371/journal.pone.0130352
|View full text |Cite
|
Sign up to set email alerts
|

Cortical and Subcortical Grey and White Matter Atrophy in Myotonic Dystrophies Type 1 and 2 Is Associated with Cognitive Impairment, Depression and Daytime Sleepiness

Abstract: ObjectivesCentral nervous system involvement is one important clinical aspect of myotonic dystrophy type 1 and 2 (DM1 and DM2). We assessed CNS involvement DM1 and DM2 by 3T MRI and correlated clinical and neuocognitive symptoms with brain volumetry and voxel-based morphometry (VBM).Methods12 patients with juvenile or classical DM1 and 16 adult DM2 patients underwent 3T MRI, a thorough neurological and neuropsychological examination and scoring of depression and daytime sleepiness. Volumes of brain, ventricles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
85
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 43 publications
10
85
1
1
Order By: Relevance
“…Similarly to previous reports, daytime sleepiness was more pronounced in patients with DM1 38. This difference was not associated with respective differences in the severity of SRBDs, BMI, or muscle weakness, the factors that may limit the restorative function of sleep and thus indirectly provoke excessive sleepiness.…”
Section: Discussionsupporting
confidence: 85%
“…Similarly to previous reports, daytime sleepiness was more pronounced in patients with DM1 38. This difference was not associated with respective differences in the severity of SRBDs, BMI, or muscle weakness, the factors that may limit the restorative function of sleep and thus indirectly provoke excessive sleepiness.…”
Section: Discussionsupporting
confidence: 85%
“…Myotonic dystrophies (DM type 1 and DM type 2) are similar but distinct multisystemic diseases related to different repeat expansion mutations which results to manifold cerebral involvement . MRI studies revealed a broad spectrum of abnormalitiers including white and grey matter abnormalities . So far, two studies evaluated TCS findings in patients with DM .…”
Section: Tcs In Depressed Patients With Association To Neurodegeneratmentioning
confidence: 99%
“…61 MRI studies revealed a broad spectrum of abnormalitiers including white and grey matter abnormalities. 62 So far, two studies evaluated TCS findings in patients with DM. 63,64 Peric et al studied 66 patients with DM type 1 and detected reduced BR echogenicity in 25 (37.7%) of them.…”
Section: Depression In Myotonic Dystrophiesmentioning
confidence: 99%
“…Other studies found an association between unstable cytosine–thymine–guanine (CTG) repeat expansion size and cognitive test performance and behavior changes in myotonic dystrophy . This is unsurprising given that, in myotonic dystrophy type 1, a positive association exists between brain pathology and CTG repeat expansion, whereas the extent of white‐matter lesions is positively correlated with cognitive impairment and behavioral symptoms . In addition, other contextual factors—which may be less dependent on underlying brain pathology—may also affect cognitive functioning.…”
mentioning
confidence: 99%
“…5,6,8 This is unsurprising given that, in myotonic dystrophy type 1, a positive association exists between brain pathology and CTG repeat expansion, 9 whereas the extent of white-matter lesions is positively correlated with cognitive impairment and behavioral symptoms. 10,11 In addition, other contextual factors-which may be less dependent on underlying brain pathologymay also affect cognitive functioning. Reactive depression, perhaps resulting from difficulties adjusting to physical symptoms, may worsen performance on cognitive testing; fatigue, sleepiness, or pain may also lead to problems with effort.…”
mentioning
confidence: 99%